АНАЛІЗ ЧАСОВИХ РЯДІВ У ПРОГНОЗУВАННІ ФІНАНСОВИХ ІНВЕСТИЦІЙ - Лубенець, С. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
In the article the basic components of a highly probable forecast efficient financial investments based on the analysis of price time series with a simple trade and investment strategy Price action, proper risk management and investment capital, as well as the proper investment of thinking based onpatience, discipline, and impartiality in making investment decisions.